Software Cost Estimation Using Function Point Analysis - Anggi Yhurinda Perdana Putri; Apol Pribadi Subriadi (Institut Teknologi Sepuluh Nopember, 2019)
Software Cost Estimation is an important activity in software development projects. Various measurement methods are widely applied to estimate software cost, and one of them is Function Point Method. Function Point (FPA) method measures the software by measuring software functionality that provided to users based on design logic. The measurement consist of several steps: calculate Unadjusted Function Point (UFP), Value Adjustment Factor (VAF), Adjusted Function Point (AFP) and estimate the software cost. Software project that became the object of this research were four licensing projects from local government with total cost 229.680.000. The estimated total cost of four projects using Function Point method is 216.956.881 rupiahs. The percentage gap between the actual with the function point that is equal to 5.54%. It can be concluded that FPA is an accurate method and this cost estimation can be used by developers in determining the cost of software to be built